Evaluating the impact of crop waterlogging and flood disasters using multi-source data: a case study of the Sanjiang Plain - Peng Wei; Huichun Ye; Chaojia Nie; Minghao Qin; Yue Zhang; Hongye Wang; Shanyu Huang; Ronghao Liu (Climate Services, 2025)
Waterlogging and flood disasters, often induced by persistent heavy precipitation, present additional hurdles to China’s agricultural resilience.. Assessing the impact of waterlogging disasters on crops is an essential basis for guiding agricultural disaster prevention and mitigation, and is of great importance for stabilizing agricultural production and ensuring food security. Taking Sanjiang Plain as the research area, this paper selected five indicators including cumulative precipitation, topography, river network, crop type, and crop vulnerability from three aspects: the risk of disaster-causing factors, the sensitivity of the disaster-bearing environment, and the vulnerability of the carrier. A waterlogging impact evaluation index system was constructed, and the weighted comprehensive evaluation method was used to evaluate the impact of crop waterlogging disasters from 2020 to 2022. The evaluation results were then verified using crop yield data. The results show that the absolute correlation coefficients (|r|) between the mean values of the composite index of waterlogging and flood influence and yields per unit area for rice, maize, and soybean were 0.69, 0.74, and 0.71, respectively. These findings highlight the accuracy of the assessment index system for crop waterlogging and flood impacts. Over time, there were noticeable fluctuations in the contribution of disaster-causing factors and the disaster-breeding environment that breed them. Spatially, the contributions of disaster-causing factors and the disaster-breeding environment were unevenly distributed, whereas the impact on the carrier remained concentrated. Consistent with natural patterns, the results of this study provide essential technical support for agricultural disaster prevention and mitigation, aiding the sustainable development of agriculture in the Sanjiang Plain.